Traction characteristics of a rolling element bearing under rapid acceleration and implications for auxiliary operation in magnetic bearing systems - Matthew O.T. Cole (2018)
The application of rolling clement bearings for auxiliary operation in magnetic bearing systems is quite common, yet such operation is very different to that for which standard bearings are designed. During initial touchdown of a spinning rotor with an auxiliary bearing, rapid acceleration of the bearing inner race results in large inertial and friction forces acting on the rolling elements. Complex dynamic behavior of the bearing assembly and resulting traction forces are difficult to predict but, nonetheless, have important implications for both rotor dynamic behavior and thermo-elastic behavior of the bearing components. The aim of this work is to obtain an insight into bearing behavior by analyzing component interaction forces that would arise based on the assumption that the overall bearing traction torque is dependent only on instantaneous load, speed and acceleration. How such an analysis can be verified by experimental measurements of traction during rapid acceleration is discussed and some initial experimental results are presented. The implications for modeling and prediction of rotor-magnetic bearing system behavior during touchdown are also discussed. Copyright © 2006 by ASME.